Ultra-wide scanning topology of the MIMO antenna array for Imaging Radar - Nikishov, Artem; Evtyushkin, Gennady; Shepeleva, Elena; Lukyanov, Anton; Kim, Jongseok; Sugiura, Tsuyoshi (IEEE Vehicular Technology Conference, 2021)
This paper presents an ultra-wide scanning topology of the multiple-input-multiple-output antenna array for Imaging Radar to be the basis for algorithms development in future implementation of AI-driven cars. Antenna array provides the ultra-wide field of view (145°) at 2.3° resolution in azimuth plane and was developed for a 79 GHz frequency modulated continuous wave radar prototype for use in autonomous vehicles (Level-4) and supports 12 transmitting and 16 receiving channels (forming 192 virtual channels). Field of view is 20° and resolution is 2.75° in elevation plane. Antenna array was installed on the vehicle as part of the Imaging Radar system. The basic performances were evaluated at field tests.